Bridging Higher Education Skills for Transformation in Southern Africa - Gilbert, Kunatsa (Quality Assurance Practices for Transformative Higher Education in Southern Africa, 2025)
A gap exists between acquired skills and the labour market in Africa. This chapter aimed to bridge the gap between learning outcomes and real-world skills to achieve Aspiration 1 of the African Union Agenda 2063. This chapter unveiled forms of assessment that are summative and formative in tertiary institutions. It also identified examinations, quizzes and projects or take-home assignments as examples of continuous assessment commonly used in assessing students in tertiary institutions, though they are associated with unethical practices in various tertiary institutions. The chapter marked the importance of feedback loops, curriculum evaluation and modification and the much-needed quality assurance in the teaching and learning process. The author used documentary analysis and online platforms to gather information. It was then discovered by the author that feedback loops are missing in tertiary institutions, which might have an impact on the promotion of innovation and creativity skills to achieve the African Union Agenda 2063.